THE EFFECT OF CSR DISCLOSURE, CORPORATE GOVERNANCE MECHANISM, AUDITOR INDEPENDENCE, AUDITOR QUALITY, AND FIRM SIZE ON EARNING MANAGEMENT - Wahyono, Wahyono; Novianto, Andrian Nur; Putri, Eskasari (Universitas Muhammadiyah Surakarta, 2019)
This study aims to determine the Effect of CSR Disclosures, Corporate Governance Mechanisms, Auditor Sensitivity, Audit Quality and Company Size on Earning Management. This study uses a quantitative research design with data on Food and Beverage companies listed on the Stock Exchange in 2014-2017. The population in this study is a Food and Beverage company registered on the Stock Exchange in 2014-2015 and has passed the research criteria. The sampling technique in this study used a purposive sampling technique that is random sampling and has passed the criteria of this study. The number of all participating data is 32 companies. The data analysis model used is a multiple linear regression model using the SPSS test tool. The results of the study show that CSR Disclosure, Corporate Governance Mechanism, Auditor Independence, Audit Quality and Company Size have no effect on Earning Management